Appropriation of public space : combining the Wayfinder methodology and tactical urbanism in a park in the city of Latacunga (2022)
The paper exposes an intervention proposal for an urban park in the city of Latacunga, Cotopaxi (Ecuador). The potential intervention seeks to promote the appropriation of public space where people and future users act as protagonists of the change, by contributing ideas and initiatives to create a place that considers their opinions, needs and suggestions. In order to achieve this, the proposal used the Wayfinder methodology, an avant-garde approach that assesses, plans, and acts in social-ecological systems to achieve sustainable, safe and fair transformations. Likewise, it proposes tactical urbanism activities as practical strategies to accomplish the project’s objective. The paper concludes that an intervention of this type is viable and capable of generating outstanding results regarding urban public space appropriation. Being viable, it is established that it can be executed in the short term, in accordance with the guidelines presented in the text.